Kejahatan Seksual Berbasis Digital: Tantangan Penegakan Hukum di Era Media Sosial - Rahmiati, Rahmiati; Latukau, Fikry; Nadila, Gesti (Legalita, 2025)
Digital-based sexual crimes are increasing along with the development of technology and social media, with the main victims being women and children. This study aims to analyze the challenges of law enforcement against digital-based sexual crimes in Indonesia and provide policy recommendations to improve the effectiveness of legal protection for victims. This study analyzes the challenges of law enforcement against these crimes and recommends solutions to improve protection for victims. Using normative legal research methods, this study found that although Indonesia has regulations such as the ITE Law and the TPKS Law, law enforcement still faces obstacles, such as the anonymity of perpetrators, lack of capacity of law enforcement officers, difficulty in proving digital evidence, and minimal international cooperation. Strategic steps are needed such as improving the expertise of officers in digital forensics, digital literacy education, strengthening regulations, and international cooperation so that law enforcement is more effective and provides optimal protection for victims.